2023
DOI: 10.1101/2023.12.22.573061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D genome organization during TGFB-induced transcription requires nuclear microRNA and G-quadruplexes

Julio Cordero,
Guruprasadh Swaminathan,
Diana G Rogel-Ayala
et al.

Abstract: Studying the dynamics of three-dimensional (3D) chromatin structure is essential to understand biological processes in the cell nucleus. Recent publications based on integrative analysis of multi-omics studies have provided comprehensive and multilevel insights into 3D genome organization emphasizing its role during transcriptional regulation. While enhancers are regulatory elements that play a central role in the spatiotemporal control of gene expression, chromatin looping has been broadly accepted as a means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Remarkably, the hexanucleotide 3′-terminal motif of miR-29b acts as a transferable nuclear localization element that directs nuclear enrichment of other miRNAs or small interfering RNAs to which it is attached. Moreover, we found by sequence alignment analysis that a partially conserved and extended version of this nuclear shuttling motif is present in mouse and human miRNAs that have been functionally characterized in the cell nucleus [ 46 ]. The presence of a nuclear shuttling motif in various miRNAs, which in turn is conserved across species, suggests the existence of a common mechanism regulating the enrichment of these miRNAs in the cell nucleus, thereby indicating that even miRNAs with common seed sequences can have diverse functions and regulatory capacities due to distinct subcellular localizations, underscoring the complexity of miRNA-mediated regulation.…”
Section: Nuclear Mirnas and Their Implications In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the hexanucleotide 3′-terminal motif of miR-29b acts as a transferable nuclear localization element that directs nuclear enrichment of other miRNAs or small interfering RNAs to which it is attached. Moreover, we found by sequence alignment analysis that a partially conserved and extended version of this nuclear shuttling motif is present in mouse and human miRNAs that have been functionally characterized in the cell nucleus [ 46 ]. The presence of a nuclear shuttling motif in various miRNAs, which in turn is conserved across species, suggests the existence of a common mechanism regulating the enrichment of these miRNAs in the cell nucleus, thereby indicating that even miRNAs with common seed sequences can have diverse functions and regulatory capacities due to distinct subcellular localizations, underscoring the complexity of miRNA-mediated regulation.…”
Section: Nuclear Mirnas and Their Implications In Cancermentioning
confidence: 99%
“…Highlighting the role of miR-9 in the cell nucleus, we recently published a sequencing experiment after chromatin isolation by miRNA purification (ChIRP-seq) in mouse lung fibroblasts showing that miR-9 is enriched at promoters and super-enhancers of genes that are responsive to tissue growth factor beta 1 (TGFB1) signaling [ 46 ]. Further, we found that nuclear miR-9 is required for chromatin features related to increased transcriptional activity, including broad domains of the euchromatin histone mark histone 3 tri-methylated lysine 4 (H3K4me3) and the non-canonical DNA secondary structures G-quadruplex (G4).…”
Section: Nuclear Mirnas and Their Implications In Cancermentioning
confidence: 99%